Design, fabrication, and testing of an automated machine for the processing of dried water hyacinth stalks for handicrafts. Issue 1 (March 2021) - Amante, K; Ho, L; Lay, A; Tungol, J; Maglaya, A; Fernando, A
Abstract: In this paper a portable machine that is capable of pressing and cutting dried water hyacinth stalks was designed, fabricated and tested. This prototype will help automate the laborious manual cutting of the water hyacinth dried stalks. The machine will flatten the dried stalks and cut stalks into three different widths of 0.5in, 0.25in, and 0.75in. This machine might improve the consistency and quality of the pre-cut stalks. This will also help workers focus on other handicraft processes such as weaving thus improving productivity and helping the local handicraft industry by providing a low-cost alternative equipment.